Response of yield increase for dryland winter wheat to tillage practice during summer fallow and sowing method in the Loess Plateau of China - Hui LI; Jian-fu XUE; Zhi-qiang GAO; Nai-wen XUE; Zhen-ping YANG (Journal of Integrative Agriculture)
Soil moisture is the most critical limiting factor impacting yields of dryland winter wheat (Triticum aestivum L.) and it is strongly affected by tillage practice and sowing methods. This study was to assess the link between sowing method and tillage practice during summer fallow and their subsequent effect on soil moisture and grain yield. Furthermore, we sought to identify a more appropriate farming management practice for winter wheat production in Loess Plateau region of China. The experiment was conducted from 2011 to 2013, using a two-factor split plot design, including subsoiling (SS) or no tillage (NT) during summer fallow for main plots, and conventional drill sowing (DS) or plastic film drill sowing (FM) for subplots. Results showed that the maximum soil water storage (SWS) was under SS×FM treatment with values of 649.1 mm (2011–2012) and 499.4 mm (2012–2013). The SWS during the 2011–2012 growing season were 149.7 mm higher than that in the 2012–2013 growing season. And adoption of SS×FM significantly increased precipitation use efficiency (PUE) and water use efficiency (WUE) compared to other treatments for both seasons. Moreover, adoption of SS×FM significantly increased yield by 13.1, 14.4, 47.3% and 25.9, 39.1, 35.7% than other three treatments during the two growing seasons, respectively. In summary, combining subsoiling during summer fallow with plastic film drill sowing (SS×FM) increased SWS at sowing and effectively improved WUE, thus representing a feasible technology to improve grain yield of dryland winter wheat in the Loess Plateau of China.